Editorial - Grimaldo Muchotrigo, Mirian (2021)
The university is an experiential space that complements basic education and offers students the possibility of expanding their reflective capacity, so that people can assume responsibility for their daily participation in the creation of the nation (Maturana, 1997). This This definition emphasizes the importance of the formative role of the university and how it is inserted in the daily life of our lives. of our lives; elements that are so necessary when we find ourselves in the midst of a pandemic that demands socially pandemic that demands socially responsible behavior, not only in the individual aspect but also collectively, as a country. collective, as a country.